A Simulation Study of the Ecological Speciation Conditions in the Galician Marine Snail Littorina saxatilis - Fernández-Meirama, M.; Rolán-Alvarez, E.; Carvajal-Rodríguez, A. (Frontiers in Genetics, 2022)
In the last years the interest on evolutionary divergence at small spatial scales has increased and so did the study of speciation caused by ecologically-based divergent natural selection. The evolutionary interplay between gene flow and local adaptation can lead to low-dispersal locally adapted specialists. When this occurs the evolutionary interplay between gene flow and local adaptation could eventually lead to speciation. The L. saxatilis system consists of two ecotypes displaying a microhabitat-associated intraspecific dimorphism along the wave-exposed rocky shores of Galicia. In spite of being a well-known system, the dynamics of the ecotype formation remains unclear and cannot be studied from empirical evidence alone. In this study, individual-based simulations were used to incorporate relevant ecological, spatial and genetic information, to check different evolutionary scenarios that could evolve non-random mating preferences and finally may facilitate speciation. As main results, we observed the evolution of intermediate values of choice which matches estimates from empirical data of L. saxatilis in Galician shores and coincides with previous theoretical outcomes. Also, the use of the mating correlation as a proxy for assortative mating led to spuriously inferring greater reproductive isolation in the middle habitat than in the others, which does not happen when directly considering the choice values from the simulations. We also corroborate the well-known fact that the occurrence of speciation is influenced by the strength of selection. Taken together, this means, also according to other L. saxatilis systems, that speciation is not an immediate consequence of local divergent selection and mating preferences, but a fine tuning among several factors including the ecological conditions in the shore levels, the selection strength, the mate choice stringency and cost to choosiness. The L. saxatilis system could correspond to a case of incomplete reproductive isolation, where choice intensity is intermediate and local adaptation within the habitat is strong. These results support previous interpretations of the L. saxatilis model system and indicate that further empirical studies would be interesting to test whether the mate choice mechanism functions as a similarity-like mechanism as has been shown in other littorinids.